Persepsi Pengunjung Terhadap Daya Tarik Wisata Berdasarkan Pull Factor Di Bendungan Batutegi Kabupaten Tanggamus Lampung - Gultom, Eklesia Armauly; Harianto, Sugeng Prayitno; Dewi, Bainah Sari; Winarno, Gunardi Djoko; Febryano, Indra Gumay (MAKILA, 2022)
The perception of visitors becomes a reference in the development of ecotourism which is influenced by pull factors that come from outside the visitors themselves. The purpose of this study was to analyze the pull factor of the tourist attraction of the Batutegi Dam. The sampling method used is using interviews using a questionnaire and calculated using a Likert scale and then analyzed by descriptive analysis. The results showed that the average visitor's perception of the pull factor was included in the category of strongly agree. This shows that the visitor's perception of the natural beauty and atmosphere of the Batutegi Dam presented is still natural. Visitors feel nostalgic when visiting Batutegi Dam. Adequate facilities and infrastructure at the Batutegi Dam make visitors come to the Batutegi Dam tourist attraction.